Catalytic Conversion of Palm Oil to Bio-Hydrogenated Diesel over Novel N-Doped Activated Carbon Supported Pt Nanoparticles - Wei Jin; Laura Pastor-Pérez; Juan J. Villora-Pico; Mercedes M. Pastor-Blas; Antonio Sepúlveda-Escribano; Sai Gu; Nikolaos D. Charisiou; Kyriakos Papageridis; Maria A. Goula; Tomas R. Reina (Energies, 2019)
Bio-hydrogenated diesel (BHD), derived from vegetable oil via hydrotreating technology, is a promising alternative transportation fuel to replace nonsustainable petroleum diesel. In this work, a novel Pt-based catalyst supported on N-doped activated carbon prepared from polypyrrole as the nitrogen source (Pt/N-AC) was developed and applied in the palm oil deoxygenation process to produce BHD in a fixed bed reactor system. High conversion rates of triglycerides (conversion of TG > 90%) and high deoxygenation percentage (DeCOx% = 76% and HDO% = 7%) were obtained for the palm oil deoxygenation over Pt/N-AC catalyst at optimised reaction conditions: T = 300 °C, 30 bar of H2, and LHSV = 1.5 h−1. In addition to the excellent performance, the Pt/N-AC catalyst is highly stable in the deoxygenation reaction, as confirmed by the XRD and TEM analyses of the spent sample. The incorporation of N atoms in the carbon structure alters the electronic density of the catalyst, favouring the interaction with electrophilic groups such as carbonyls, and thus boosting the DeCOx route over the HDO pathway. Overall, this work showcases a promising route to produce added value bio-fuels from bio-compounds using advanced N-doped catalysts.